Pediatric Train Injuries: A 10-Year Review From the Pennsylvania Trauma Outcomes Study Database. Issue 2 (February 2022) - Pennell, Christopher; Lindholm, Erika; Latreille, Jacob; Kadakia, Shreeja; Nanassy, Autumn; Ciullo, Sean; Arthur, L. Grier; Grewal, Harsh; Prasad, Rajeev
Abstract : Objectives: Trains can cause severe injuries in pediatric patients requiring significant resource utilization. We sought to review train injuries in Pennsylvania to determine the burden of these injuries on the pediatric trauma system. Methods: We queried the Pennsylvania Trauma Outcomes Study Database to identify patients younger than 18 years injured by trains between 2007 and 2016. Demographics, hospital course, outcomes, and resource utilization were reviewed. Results: Thirty-five children from 17 Pennsylvania counties were included. Three counties accounted for 48.6% of injured children. The median age was 15.0 years, and most patients were White (60.0%) and male (77.1%). The median length of stay was 8.0 days and overall mortality 8.6%. Intensive care unit admission was required for 65.7%. The median Injury Severity and Functional Status at Discharge scores were 14.0 and 18.0, respectively. Major orthopedic injuries (fracture or amputation) were the most common (57.1%) followed by traumatic brain injury (45.7%), pneumothorax (14.3%), and solid organ injury (14.3%). Operative management was common with 65.7% undergoing surgery. Conclusions: Injuries caused by trains can be severe and are most commonly orthopedic or traumatic brain injuries. Targeted safety interventions may be possible given the common mechanisms and geographic clustering of these injuries.